Trocar-guided trans-vaginal mesh surgery for pelvic organ prolapse: effects on urinary continence and anatomical and functional outcomes. A prospective observational study. (March 2017) - Natale, F.; Costantini, E.; La Penna, C.; Illiano, E.; Balsamo, R.; Carbone, A.; Cervigni, M.
Abstract: Objective: Primary objective of this study was to assess the effects of trocar-guided transvaginal mesh surgery (TVM) on cure and prevention rates for incontinence, without concomitant surgery for Stress Urinary Incontinence (SUI). Our secondary objectives were anatomical outcomes, relief of symptoms and effect on quality of life (QoL). Study design: This prospective observational study evaluated women who underwent TVM for symptomatic stage >2 Pelvic Organ Prolapse (POP). SUI was evaluated objectively using the cough stress test with prolapse reduced. SUI and urge urinary incontinence (UUI) were subjectively evaluated using ICIQ-SF. Anatomical cure was defined as stage <2 at POP-Q. Statistical analysis: McNemar chi-square test; paired t-test; Mann–Whitney test. Results: Seventy-two patients reached final evaluation (mean follow-up 72 months). In the 40 pre-op continent patients, 34 (85%) remained continent postoperatively and 6 (15%) showed de novo SUI. Only 1 patient chose to undergo subsequent TVT. The number needed to treat was 6 to prevent 1 women developing de novo objective SUI and 39 to prevent 1 woman having to undergo SUI surgery. In the 32 pre-op incontinent patients, 18 (56.3%) became continent postoperatively. Only 1 patient chose to undergo subsequent TVT. UUI was present in 44 patients pre-operatively and 15 (20.8%) post-operatively (1 de novo ). Forty-four patients (61.1%) were continent post-operatively for SUI and UUI. We observed a significant improvement in storage, voiding, post-micturition and prolapse-related symptoms. The anatomical cure rate was 87.5% for the anterior compartment and 90.3%.for the apical segment. The apical recurrence was 8.3% in the patients previously hysterectomised, 18.8% in the patients with uterus preservation and 0% in the patients with concomitant hysterectomy. QoL scores improved in all domains except sleep and personal relationships. We observed mesh exposure in 10 patients (13.9%), in 5 of whom it was associated with a concomitant hysterectomy Conclusions: TVM showed excellent results in terms of continence and can be performed without contemporary anti-incontinence surgery, for both continent and incontinent women. Patients should have pre-operative counselling before POP surgery. For severe uterine prolapse the Perigee™ System should be employed with concomitant hysterectomy because uterus preservation is associated with significantly higher apical recurrence rates.